Characterization of ZnO as substrate for DSSC - Mansilla Wettstein, Candela (2018)
We present a complete analysis of the photoinjection process in 3 nm spherical ZnO nanoparticles with different dyes attached to their surface. The study was carried using a TD-DFTB model to describe the quantum dynamics of charge transfer in the presence of an external time dependent electric field simulating resonant illumination. The ZnO + dye systems have been classified according to the injection process (type I and type II) that they present. In addition, the calculated charge transfer shows that many dyes present hole injection into the nanoparticle. We have classified the charge transfer into holes or electron and compare these results with the TiO2 + dye system obtained from the literature.